THE DIRECTING SCHOOL OF THE SYRDARYA THEATRE (1978–1991): ISSUES OF PRESERVING AND DIGITISING THEATRE HISTORY - Abdumuxtorova Nazokat (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article analyses the period of creative maturity of the Syrdarya Regional Musical Drama Theatre between 1978 and 1991. It examines the directing school formed under Makhkam Muhammedov (1978–1982) and Jura Mahmudov (1983–1994), the distinctive stage solutions of Richard III (1980) and King Lear (1990), and the creative partnership with Mashrab Boboyev. The article also addresses the theatre’s bilingual repertoire policy. Theatre documents — programmes, newspaper reviews, actors’ memoirs — are currently preserved mainly on paper, and many have been lost. The article proposes practical approaches to digitising these materials in order to preserve them for future generations and bring them into scholarly circulation.